Wide-field OCT-angiography assessment of choroidal thickness and choriocapillaris in eyes with central serous chorioretinopathy - Meng, Yang; Xu, Yishuang; Li, Lu; Su, Yu; Zhang, Lu; Chen, Changzheng; Yi, Zuohuizi (Frontiers in Physiology, 2022)
Purpose: To assess wide-field changes in choroidal thickness and choriocapillaris in eyes with central serous chorioretinopathy (CSC) compared with the fellow eyes and eyes from healthy individuals using wide-field swept-source (SS) OCT-Angiography (OCTA). Methods: A cross-sectional study in which 68 eyes from 34 individual patients affected by unilateral CSC and 32 eyes of 32 age- and sex-matched healthy subjects were evaluated. All subjects underwent wide-field SS-OCTA examination to quantify choroidal thickness and vascular density of the choriocapillaris. To assess the wide-field changes, we developed five 4-by-4 mm square regions located in the posterior pole and in the four quadrants of the peripheral retina (superotemporal, inferotemporal, superonasal, and inferonasal subfields, respectively). Results: The choroidal thickness of eyes with CSC was greater than that of the fellow eyes in the central and inferonasal subfields (p <0.001 for the central subfield and p = 0.006 for the inferonasal subfield, respectively). Compared with the choroidal thickness of healthy eyes, that of patients with CSC were significantly greater in all the subfields (p < 0.05 for the fellow eyes and p <0.05 for eyes with CSC, respectively). Compared with that of healthy eyes, the vascular density of choriocapillaris in eyes of patients with CSC were significantly greater in the central and superotemporal subfields (p < 0.05 for the fellow eyes and p <0.05 for eyes with CSC, respectively). In the central region, the vascular density of choriocapillaris of the fellow eyes was greater than eyes with CSC (p =0.023). Conclusions: CSC appears to be a bilateral disease with asymmetric manifestations. Local factors of the diseased eyes may play an important role in the development of CSC, during which dynamic and regional changes in the choriocapillaris have happened. Wide-field swept-source OCTA provided a useful tool to study the pathogenesis of CSC.